Cognitive Apprenticeship Strategies for the Media Literacy Classroom - Nate Floyd; Jaclyn Spraetz (Communications in Information Literacy)
Inspired by the apprenticeship model of teaching and learning, two instructors report on their efforts to place current events at the center of a semester-long media and information literacy course. They discuss strategies to harness curiosity about contemporary topics (e.g., misinformation, climate change, algorithms, right-to-repair, blockchain, artificial intelligence, etc.), and create engagement-driven course content. The paper provides concrete examples of activities and assignments used to situate learning in real-world contexts and build students' confidence in navigating information independently. This case study offers insights for other educators seeking to apply cognitive apprenticeship principles to media and information literacy instruction.